2022
DOI: 10.3390/cancers14102469
|View full text |Cite
|
Sign up to set email alerts
|

Local and Regional Therapies for Hepatocellular Carcinoma and Future Combinations

Abstract: Background: Hepatocellular carcinoma (HCC) can be treated by local and regional methods of percutaneous interventional radiological techniques. Indications depend on tumor size, type and stage, as well as patient’s condition, liver function and co-morbidities. According to international classification systems such as Barcelona Clinic Liver Cancer (BCLC) classification, very early, early or intermediate staged tumors can be treated either with ablative methods or with transarterial chemoembolization (TACE), dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 182 publications
0
8
0
Order By: Relevance
“…Second, we examined patients underwent only TACE as first-line treatment. Nowadays a lot of research has been made in adjuvant immuno therapy after TACE in advanced-stage HCC patients ( 47 52 ). Combining TACE with immunotherapeutic agents hypothesized that prolonged survival could be achieved because adjuvant immunotherapy can control TACE-induced neo-angiogenesis and reduce the risk of tumor recurrence and metastatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we examined patients underwent only TACE as first-line treatment. Nowadays a lot of research has been made in adjuvant immuno therapy after TACE in advanced-stage HCC patients ( 47 52 ). Combining TACE with immunotherapeutic agents hypothesized that prolonged survival could be achieved because adjuvant immunotherapy can control TACE-induced neo-angiogenesis and reduce the risk of tumor recurrence and metastatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy may upregulate the expression of both antigen-presenting cells as well as effector T cells and increase overall T-cell infiltration into tumors, and thus enhancing the effects of immunotherapies [ 25 ]. Furthermore, locoregional treatments might enhance local hypoxia and vascular permeability, induce immunogenicity via the release of tumor antigens following cancer cell death, and elicit damage-associated molecular patterns, which might be rescued by TKIs and ICIs [ 26 ]. It has also been reported that SBRT is particularly effective in tumor areas with high oxygenation, namely the tumor periphery, where TACE itself is less effective [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapy information included surgeries, radiotherapy, and chemotherapy. Patients were divided into five surgery groups: non-surgery, LTD, WSR, LR, and LT ( 6 , 18 ). LTD comprised RFA, cryosurgery, alcohol [percutaneous ethanol injection (PEI)], and photodynamic therapy (PDT).…”
Section: Methodsmentioning
confidence: 99%